Numerical investigation of the direct tensile behaviour of laminated and transversely isotropic rocks containing incipient bedding planes with different strengths - Shang, Junlong (2020)
The anisotropic direct tensile behaviour of laminated and transversely isotropic Midgley Grit sandstone (MGS) was investigated in this paper using a particle-based discrete element method (DEM) with consideration of the incipiency of bedding planes. Laboratory experiments were conducted to quantify the direct tensile strength of the incipient bedding planes, and the results were used to calibrate the numerical model. The effects of bedding planes with different relative positions and spacing were discussed. A comparison between the simulated results of this study and the predicted results from failure criteria was completed, and a good agreement was observed.